Tuning the Emission Behaviour of Halogenated Bridged Ethers in Solution, as Solids and as Aggregates by Chalcogen Substitution. Issue 1 (1st October 2022) - Dubbert, Justin; Valtolina, Marco; Huber, Alexander; Scherz, Tim D.; Wölper, Christoph; Daniliuc, Constantin G.; Filiba, Ofer; Sen, Saumik; Schapiro, Igor; Rizzo, Fabio; Voskuhl, Jens
Abstract: In this contribution, we describe a set of three chlorinated bridged ethers with varying numbers of sulfur and oxygen atoms. The substitution leads to highly emissive compounds with tunable photophysical properties in relationship to their state of aggregation, i. e. in solution, as aggregates and in the solid state. Additionally, an in‐depth X‐ray diffractometric analysis supported by a Hirshfeld study of non‐covalent interactions and quantum chemical simulations was carried out. As the outcome, it was found that the content of sulfur in the compounds regulates the tuning of emission in solution as well as in the aggregated states as a consequence of their variation of planarity. Abstract : Building a bridge : An easy accessible platform, based on bridged, halogenated ethers, for emission tuning depending on the aggregation state, is presented. The photophysical properties and molecular packing in the crystal lattice of the three designed compounds were investigated. The experimental results were corroborated by DFT‐based simulations.